MBTI Dichotomies and Speaking Achievement Analysis of English Tadris Students - Nabilah Fairuz R; Mukrim Mukrim (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2026)
This study aims to know whether there is a difference between the MBTI dichotomies on students' speaking achievement and how the variety of MBTI dichotomies influences students' speaking achievement. This study was conducted using mixed methods with an explanatory sequential design. The sampling technique used was non-probability sampling; purposive sampling. The sample was Tadris English students' class of 2022 of UIN Datokarama Palu. The research sample consisted of 29 students, 8 of them were informants for the interview. The quantitative data as the core data were analyzed using SPSS, precisely the One Way ANOVA test, revealing that there is no difference in students' speaking achievement between extrovert-introvert, sensing-intuition, thinking-feeling, and judging-perception. Moreover, the absence of differences in results influences the MBTI varieties, indicating that MBTI dichotomies do not influence students' speaking achievement. In addition, based on the findings per trait, there is no influence on students' Extrovert, Introvert, Thinking, and Feeling beliefs in the speaking class; the assessment focused on students' activeness in speaking. Meanwhile, students Sensing, Intuiting, Judging, and Perceiving stated that the evaluation was based on the answers presented in speaking class and the demands of the answer in the form of the question to be answered. Therefore, the study assumed that students' personalities changed in speaking performance. Thus, there was no difference and no influence on speaking achievement based on the MBTI dichotomies because several factors influenced these changes. The factors are the demands of the goals, the precision of answers based on context, and the demands for activeness in speaking class. These findings have significant implications for English language education and psychology, challenging the traditional belief in the influence of MBTI dichotomies on students' speaking achievement.